Not to be confused with H function.
H* Function
Growth rate
Based On

The H* function (defined by SuperJedi224 for generating very large "-illions") is defined as follows:

  • H*(m)=H(m)=103m+3
  • H*(m,0)=m
  • H*(m,n)=H(H(H(...H(m)...))), with H*(m,n-1) Hs.
  • H*(a,...,b,c,1)=H*(a,...,b,c)
  • H*(a,...,b,c,d)=H*(a,...,b,H*(a,...,b,c,d-1))

Source: [1]

See also: Extended H* Function

Ad blocker interference detected!

Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.